The sketchbook as a resource to encourage the creative experience in Contemporary Art education (Revista Apotheke, 2021)
The article seeks to problematize the use of the sketchbook as a didactic tool that helps and enhances the development of the creative process in art education, relating it to Contemporary Art. It also emphasizes the importance of stimulating creativity in students, an important skill, not only for teaching, but also for contemporary life, seeking to demystify some myths related to creation. To this end, we bring authors such as Charles Watson (2020), John Dewey (2010), Belidson Dias and Rita L. Irwin (2013), Icleia B. Cattani (2007), and others, in order to support and justify active methodologies based on practical experience of the learner, as well as creativity in art teaching. We present Brazilian and contemporary artists who use sketchbook as a means to stimulate creative thinking in their poetic process. Furthermore, we report particular experiences with our own sketchbooks and with the application of classes